(Table 3) Stratigraphy, sedimentation rates, and mass accumulation rates from DSDP Leg 92 holes - Rea, David K; Leinen, Margaret W (Supplement to: Rea, DK; Leinen, MW (1986): Neogene controls on hydrothermal activity and paleoceanography of the Southeast Pacific Ocean. In: Leinen, M; Rea DK; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 92, 597-617, https://doi.org/10.2973/dsdp.proc.92.140.1986, 1986)
The Glomar Challenger crossed the East Pacific Rise at 19°S on Leg 92 during the austral fall of 1983. The intent of the cruise was to recover sediments and rocks that would reveal the geologic history of seafloor hydrothermal activity as determined by the geochemistry and sedimentation history of hydrothermal material, the advection of sediment pore waters, the nature and history of alteration of seafloor basalt, and the paleoceanography of the southeast Pacific. Results show that the composition of hydrothermal material is determined by its source and modified by exposure to seawater during transport in the water column. The flux of hydrothermal sediment appears to increase during episodes of tectonic activity and ridge jumps but to be independent of spreading rate. Pore water advection in sediment may occur early in the depositional history of a site, but it does not appear to continue for more than 1 or 1.5 m.y. The basaltic rocks recovered are mostly low-olivine tholeiites, but those recovered at two sites contain ferrobasalt and alkali basalt. Hole 597C is the deepest penetration by the Deep Sea Drilling Project of fast-spreading crust. Basalts from that hole reveal three stages of alteration: an early deuteric stage, a reducing stage, and a later oxidative stage. K/Ar dates of alteration minerals suggest that alteration continues for 9 to 15 m.y. after the formation of crust. Paleoceanographic studies have defined the Neogene history of the compensation depth and lysocline, the timing of important changes in atmospheric transport processes, and the nature and age of significant intervals of reworking in the abyssal sediments.